Generation of Complex Syngeneic Liver Organoids from Induced Pluripotent Stem Cells to Model Human Liver Pathophysiology. Issue 3 (8th March 2022) - Raggi, Claudia; Selleri, Silvia; M'Callum, Marie‐Agnes; Paganelli, Massimiliano
Abstract: The study of human liver pathophysiology has been hampered for decades by the lack of easily accessible, robust, and representative in vitro models. The discovery of induced pluripotent stem cells (iPSCs)—which can be generated from patients' somatic cells, engineered to harbor specific mutations, and differentiated into hepatocyte‐like cells—opened the way to more meaningful modeling of liver development and disease. Nevertheless, representative modeling of many complex liver conditions requires the recreation of the interplay between hepatocytes and nonparenchymal liver cells. Here we describe protocols we developed to generate and characterize complex human liver organoids composed of iPSC‐derived hepatic, endothelial, and mesenchymal cells. With all cell types derived from the same iPSC population, such organoids reproduce the liver niche, allowing for the study of liver development and the modeling of complex inflammatory and fibrotic conditions. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Differentiation of human iPSCs into hepatic progenitor cells (hepatoblasts) Basic Protocol 2 : Differentiation of human iPSCs into endothelial progenitor cells Support Protocol 1 : Characterization of iPSC‐derived endothelial progenitor cells Basic Protocol 3 : Differentiation of human iPSCs into mesenchymal progenitor cells Support Protocol 2 : Characterization of iPSC‐derived mesenchymal progenitor cells Basic Protocol 4 : Generation of complex syngeneic liver organoids